Ionic 4,4‘-Biphenylene-Bridged Bis-ruthenium Complexes [Ru2(4,4‘-{C6H2(CH2NMe2)2-2,6}2)(terpy)2] n + (n = 2 and 4) and Their Reversible Redox Interconversion: A Molecular Switch - Steenwinkel, Pablo; Grove, David M; Veldman, Nora; Spek, Anthony L; van Koten, Gerard (Organometallics, 1998)
Copper(II)-mediated oxidative coupling of the blue, 18-electron mononuclear complex [RuII{C6H3(CH2NMe2)2-2,6}(terpy)]Cl, 3 (terpy = 2,2‘;6‘,2‘‘-terpyridine), affords the unique diamagnetic, binuclear 34-electron complex [(RuIII)2(4,4‘-{C6H2(CH2NMe2)2-2,6}2)(terpy)2](CuCl2)4, 5a. This intensely green complex has been the subject of an X-ray crystal structure determination, and the molecular geometry of the tetracation shows the C4−C4‘-coupled bridging biphenylene dianion to be planar. Two-electron reduction of this tetracation as its PF6 - salt, 5b, with N2H4·H2O affords the corresponding dicationic intensely blue, 36-electron complex [(RuII)2(4,4‘-{C6H2(CH2NMe2)2-2,6}2)(terpy)2](PF6)2, 8. An X-ray crystal structure determination of 8 shows a molecular geometry in which the bridging biphenylene dianion is nonplanar, with the metal coordination planes twisted by ca. 36° relative to each other. Cyclic voltammetry data show that the reduction of 5b (4+) to 8 (2+), i.e., [RuIII−RuIII] to [RuII−RuII], is reversible. This reduction proceeds through the mixed valence 35-electron [RuII−RuIII] complex [(RuII)(RuIII)(4,4‘-{C6H2(CH2NMe2)2-2,6}2)(terpy)2]3+, 9 (3+), which is intensely purple and which can be independently prepared by mixing acetonitrile solutions of equimolar amounts of 5 (4+) and 8 (2+).